Cultured autologous fibroblasts augment epidermal repair - Svensjö, Tor; Yao, Feng; Pomahač, Bohdan; Winkler, Thomas; Eriksson, Elof (Transplantation, 2002)
BACKGROUND: Autologous dermal fibroblasts may be useful in the treatment of skin wounds and for the enhancement of keratinocyte proliferation. This paper addressed the following questions: (1) can cultured fibroblasts (CF) be transplanted as suspensions to full-thickness skin wounds and do they influence wound healing; (2) will the transplanted CF be integrated into the new dermis; (3) can a transgene that encodes a secretable marker, human epidermal growth factor (hEGF), be expressed in the wound fluid by the transplanted CF; and (4) do CF cotransplanted with cultured keratinocytes (CK) influence the rate of wound healing? METHODS: Suspensions of CF were transplanted alone or together with CK to full-thickness wounds covered with liquid-containing chambers in an established porcine model. RESULTS: Transplantation of CF accelerated reepithelialization as determined from wound histologies and sequential measurements of protein efflux over the wound surface. CF transfected with a marker gene, beta-galactosidase, resulted in in vivo gene expression and demonstrated that transplanted CF integrated into the developing dermis. Transplantation of hEGF gene-transfected CF resulted in significant hEGF expression in wound fluid. The hEGF levels peaked at day 1 (2450 pg/ml) and then sharply decreased to low levels on day 6. CF cotransplanted with CK led to greater number of keratinocyte colonies in the wound and accelerated reepithelialization as compared with CK alone. CONCLUSIONS: Transplanted CF integrated into the dermis, accelerated reepithelialization, and improved the outcome of CK transplantation. CF may also be used for the expression of transgenes in wound and wound fluid.
Keywords: Animals; suspenze; keratinocyty; Transgenes; Keratinocytes; Fibroblasts; Wound Healing; autologní transplantace; Suspensions; prasata; kůže; fibroblasty; kultivované buňky; transgeny; epidermální růstový faktor; Cells, Cultured; Skin; Swine; hojení ran; zvířata; Transplantation, Autologous; Epidermal Growth Factor